Scientific rigour in psycho-oncology trials: why and how to avoid common statistical errors. - Bell, Melanie L; Olivier, Jake; King, Madeleine T (Psycho-Oncology, 2013)
OBJECTIVE: It is well documented that statistical and methodological flaws are common in much of the health research literature, including psycho-oncology. These can have far-reaching effects, including the publishing of misleading results; the wasting of time, effort, and financial resources; exposure of patients to the potential harms of research and decreased confidence in science and researchers by the public. METHODS: Several of the most common statistical errors and methodological pitfalls that occur in the field of psycho-oncology are discussed, including those that occur at the design, analysis, reporting and conclusion stages. RESULTS: Fourteen topics are briefly discussed, explaining why there is a problem and how to avoid it. These include proper approaches to power, clustering, missing data, categorization of continuous variables, subgroup analyses, multiple comparisons, statistical interactions, confidence intervals and correct interpretation of p-values. Extensive referencing points the reader to more in-depth explanations. CONCLUSIONS: To increase the scientific rigour in psycho-oncology, researchers should involve a biostatistician from the beginning of the study and should commit to continuing education on best practices in the fields of statistics and reporting. Copyright © 2012 John Wiley & Sons, Ltd.